USE OF TELECOMMUNICATION TECHNOLOGIES WHEN USING UNMANNED AERIAL VEHICLES FOR MONITORING THE CONDITION OF HIGH-VOLTAGE POWER LINES - VYSHNEVSʹKYY, SVIATOSLAV; LAZARENKO, SEMEN; YANITSKYI, ANATOLII; KHEBDA, ALIONA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is devoted to the improvement of monitoring processes for high-voltage power transmission lines through the application of unmanned aerial vehicles (UAVs). The study defines the fundamental principles for diagnosing power supply systems of industrial enterprises and other energy network facilities using UAVs and modern telecommunication technologies. It is proposed to integrate diagnostic procedures into UAV-based monitoring for assessing the operational condition of high-voltage transmission lines, taking into account the specific features of periodic condition control with arbitrary discreteness.Thus, the paper considers the conceptual feasibility of employing advanced telecommunication tools in combination with UAVs for diagnosing electrical systems located in hard-to-reach or hazardous areas. Particular attention is given to high-voltage power line complexes, which under wartime conditions are considered critical for ensuring the continuity of electricity supply services.Unmanned aerial vehicles (UAVs), or drones, are regarded as innovative solutions for monitoring the condition of high-voltage power lines as elements of critical infrastructure that ensure the uninterrupted delivery of electrical energy. This is especially relevant in cases where traditional inspection methods—such as manual surveys or piloted aircraft—are labor-intensive, costly, and potentially dangerous.The study discusses the use of modern telecommunication means to obtain high-resolution video and imaging during visual inspections, thermal imaging for detecting overheating and other electrical faults, LiDAR data for 3D mapping, and sensor readings such as temperature, humidity, and other environmental and operational parameters. These data are utilized to enhance the reliability and efficiency of high-voltage line condition monitoring systems.
Keywords: unmanned aerial vehicles; monitoring; telecommunication technologies; high-voltage power transmission lines; diagnostics